Safety and efficacy of a feed additive consisting of endo‐1,4‐β‐xylanase produced by Komagataella phaffii ATCC PTA‐127053 (Xygest™ HT) for all Suidae (Kemin Europa N.V) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2024)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of endo‐1,4‐β‐xylanase produced by Komagataella phaffii ATCC PTA‐127053 (Xygest™ HT) as a zootechnical feed additive (functional group: digestibility enhancers) for all Suidae at a recommended minimum level of 90,000 U/kg complete feed for pigs in the growing period and 45,000 U/kg complete feed for sows. The production strain is considered suitable for the qualified presumption of safety (QPS) approach to safety assessment. The FEEDAP Panel concluded that the additive is safe at the minimum recommended use level for all growing Suidae and all sows in the lactating phase. Xygest™ HT was considered safe for the consumers and for the environment when used in feed for all Suidae. The additive was considered not to be irritant to eyes and skin, but was considered as a dermal and respiratory sensitiser. In the absence of sufficient data, the FEEDAP Panel was not in the position to conclude on the efficacy of Xygest™ HT for all Suidae.